PHF20 Promotes Glioblastoma Cell Malignancies Through a WISP1/BGN-Dependent Pathway - Ma, Qianquan; Long, Wenyong; Xing, Changsheng; Jiang, Chongming; Su, Jun; Wang, Helen Y.; Liu, Qing; Wang, Rongfu (Frontiers in Oncology, 2020)
Glioblastoma(GBM) stem cells are resistant to cancer therapy, and therefore responsible for tumor progression and recurrence after conventional therapy. However, the molecular mechanisms driving the maintenance of stemness and dedifferentiation are poorly understood. In this study, we identified plant homeodomain finger-containing protein 20 (PHF20) as a crucial epigenetic regulator for sustaining the stem cell-like phenotype of GBM. It is highly expressed in GBM and tightly associated with high levels of aggressiveness of tumors and potential poor prognosis in GBM patients. Knockout of PHF20 inhibits GBM cell proliferation, as well as its invasiveness and stem cell-like traits. Mechanistically, PHF20 interacts with WDR5 and binds to the promoter regions of WISP1 for its expression. Subsequently, WISP1 and BGN act in concert to regulate the degradation of β-Catenin. Our findings have identified PHF20 as a key driver of GBM malignant behaviors, and provided a potential target for developing prognosis and therapy.